2009
DOI: 10.1093/humrep/den368
|View full text |Cite
|
Sign up to set email alerts
|

A controlled randomized trial evaluating the effect of lowered incubator oxygen tension on live births in a predominantly blastocyst transfer program

Abstract: The overall increase in live births demonstrated by this study indicates that the effort and expense to culture embryos in a low-O(2) environment is justified. The study was registered at clinicaltrials.gov. NCT00708487.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 28 publications
4
91
0
10
Order By: Relevance
“…All of them were prospective, but the randomization methods they used for examining the differences between the two oxygen concentrations from fertilization to ongoing pregnancies and live births are problematic. Randomization was either based on day of admission to the IVF laboratory [1], age of the woman, infertility factor, amount of gonadotrophins, number of retrieved oocytes [17], or per patient [15,19,27]. They all saw higher implantation, pregnancy and birth rates with reduced O 2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of them were prospective, but the randomization methods they used for examining the differences between the two oxygen concentrations from fertilization to ongoing pregnancies and live births are problematic. Randomization was either based on day of admission to the IVF laboratory [1], age of the woman, infertility factor, amount of gonadotrophins, number of retrieved oocytes [17], or per patient [15,19,27]. They all saw higher implantation, pregnancy and birth rates with reduced O 2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a Cochrane review [3], based on three studies that are cited in the current study [16,19,27], found evidence of a beneficial effect of culturing in low oxygen concentrations for the live birth rate (OR 1.39; 95 % CI 1.11 to 1.76; P=0.005; I2=0 %); this would mean that a typical clinic could improve a 30 % live birth rate using atmospheric oxygen concentration to somewhere between 32 % and 43 % by using a low oxygen concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our second model of environmental stress examined the effect of incubator oxygen tension on mRNA abundance and stability. Mouse studies have shown for some years (Harlow & Quinn 1979), but more recently human studies have also shown improved developmental and pregnancy rates (Kovacic & Vlaisavljević 2008, Meintjes et al 2009, Waldenström et al 2009) when cultured under a lower oxygen tension (5%) than conventionally used (20%). Furthermore, high oxygen tension greatly increases the number of genes aberrantly expressed in the mouse embryo (Rinaudo et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Various factors, such as the culture medium characteristics [2,4,41], the laboratory conditions [23,27,46], the oocyte quality [6,18], and the sperm origin [32], may be responsible for this variation in the rate of blastocyst formation. However, the influence of the patient and cycle characteristics on blastocyst formation is not understood.…”
Section: Introductionmentioning
confidence: 99%